Teicoplanin versus nafcillin and vancomycin in the treatment of experimental endocarditis caused by methicillin-susceptible or -resistant Staphylococcus aureus. - Chambers, H F (1984)
In rabbits with experimentally induced endocarditis, the efficacy of teicoplanin compared favorably both with that of nafcillin for infection by a methicillin-susceptible strain of Staphylococcus aureus and with that of vancomycin for infection by a methicillin-resistant strain of S. aureus. In a 4-day treatment regimen, teicoplanin was as effective as either nafcillin or vancomycin in eliminating organisms from aortic valve vegetations in the respective infection. In a 10-day regimen for methicillin-resistant S. aureus endocarditis, both teicoplanin and vancomycin sterilized the vegetations of some rabbits, but the relapse rate was high for both. These results justify further investigation into the role of teicoplanin for the treatment of serious infections caused by S. aureus.